DOZ047.97: Anastomotic strictures in patients with oesophageal atresia systematically treated with PPI: prospective cohort study over 10 years. (24th June 2019) - Grunder, F R; Petit, L M; Ezri, J; Jantchou, P; Aspirot, A; Faure, C
Abstract: Objectives and Study: Clinical course in oesophageal atresia (OA) patients is frequently complicated by gastroesophageal reflux disease, which is thought to be a risk factor for formation of anastomotic strictures. It is currently recommended that OA patients be treated systematically with proton pump inhibitors (PPI) after surgical repair. However, it is not clear if PPI treatment does really prevent the formation of anastomotic strictures and reduce the incidence of histological complications during long-term follow up. This study aimed to describe the outcomes of a cohort of OA patients with or without tracheoesophageal fistula (TOF) systematically treated with PPI since the neonatal period. Method: Prospective longitudinal cohort study over 11 years of 73 children with OA-TOF, systematically treated with PPI, was carried out. Descriptive data is presented as median (interquartiles) for continuous variables and as frequency (%) for categorical variables. Pearson's χ 2 test, Fisher's exact test, and Wilcoxon rank sum test were used for univariate analysis. SAS software, version 9.3 (SAS Institute, Cary, NC) was used; P -values < 0.05 were considered statistically significant. Results: Seventy-three patients (41 males) were included in the final analysis. The median age at study completion was 4.87 years (3.64, 7.97; range 1–11.4). According to Gross classification, 64 patients (88%) had OA type C, 8 (11%) had type A, and 1 (1%) had type D; long-gap OA was present in 16 patients (22%). Thoracotomy was performed in 56 patients and thoracoscopy in 17. Anastomotic strictures and recurrent strictures were diagnosed in 32 (44%) and 17 patients (23%), respectively. In all but one case, strictures occurred when the child was on PPI. Anastomotic strictures occurred significantly more frequently in long-gap OA, in patients with anastomotic leak after surgical repair and longer hospital stay ( P  = 0.02, 0.002, and 0.02 respectively). Histological complications, especially gastric metaplasia, appeared more frequently in OA patients with anastomotic strictures ( P  = 0.01). Conclusion: Forty-two percent of patients developed anastomotic strictures on PPI treatment, therefrom 55% patients with recurrent anastomotic strictures, indicating that acid gastroesophageal reflux seems not to be the major trigger factor for developing anastomotic strictures. A more selective prescription of PPI should be discussed.